Rethinking empowerment : gender and development in a global/local world - Parpart, Jane L.; Rai, Shirin; Staudt, Kathleen A. (Routledge/Warwick studies in globalisation., 2003)
'Rethinking Empowerment' looks at the changing role of women in developing countries and rejects the established notion that empowerment in development is best understood and pursued at a local/global level.